(untitled) (Estudios humanísticos. Geografía, historia y arte, 1988)
This word is trying to investigate in two important aspects the imperial roman propaganda through numismatics, we refer to the concepts of Aeternitas and Consecratio, both within the ritual of the Apoteosis which was awarded the Roman emperors and members of the imperial family after their death. Apart from the classical sources, this study of coins is the best source which fells us about these concepts; All taken from the II century A.D. from governments of Trajano to Antonino Pio. This being the period in which more emphasis was used.